Dynamic behavior and transfer function of collector field in once-through DSG solar trough power plants. (15th February 2017) - Guo, Su; Liu, Deyou; Chu, Yinghao; Chen, Xingying; Xu, Chang; Liu, Qunming; Guo, Tiezheng
Abstract: Dynamic modeling and analysis for once-through direct steam generation (DSG) solar trough are difficult because of the phase changes of the fluid and the discontinuity of fluid properties. This work develops a Collector Field Dynamic Model (CFDM) for the collector field of once-through DSG solar trough. Dynamic behaviors of fluid parameters are analyzed when there are disturbances in either full or partial small Direct Irradiance (DNI), inlet mass flow rate, and spray water flow rate. Transfer functions of outlet fluid temperature and mass flow rate are derived using the CFDM. Key results are concluded: (1) DNI disturbances closer to the subcooled water region have the largest impact on fluid parameters. (2) In initial period, the outlet temperature and mass flow rate are mainly influenced by the DNI disturbance closer to the field outlet and on the mid-section of the collector loop, respectively. (3) When the field inlet mass flow rate increases slightly, the outlet fluid temperature and mass flow rate will change significantly and take a long time to achieve new balances. (4) The outlet fluid temperature and mass flow rate change quickly and noticeably with the change in spray flow rate, and converge rapidly to new balance levels. Highlights: A nonlinear dynamic model of once-through DSG solar trough has been developed. DSG collector loop and the spray attemperator are modeled, respectively. The dynamic behaviors of the collector field are simulated and analyzed. Irradiance disturbance at subcooled water region shows larger impact on the system. Transfer functions of outlet fluid temperature and mass flow rate are derived.